IMPLEMENTASI RENCANA STRATEGIS KEMENTERIAN KESEHATAN RI TAHUN 2015-2019 DENGAN KEJADIAN ANGKA KEMATIAN IBU DI KOTA TANGERANG SELATAN - Kerin Novika (2020)
Human development is one of the judgements of a country where human quality is the capital related to the enhancement of the nation's development. Every country certainly has the hope and the relevant longterm health goals. WHO and various other international institutions have set the maternal mortality rate as one of several indicators to assess the health degree of a nation. This research aims to know what and how successful implementation of policies and programs of the South Tangerang city government in an effort to decrease the incidence of maternal mortality. Data collection is conducted using in-depth interview techniques and includes a supporting document's related to the research topic. The results showed that the role of policy and implementation programs is organized to walk synergies so the city of South Tangerang becomes a low region of the incidence of maternal mortality in Banten province.